COST-EFFECTIVENESS OF THE INTRAVENOUS MEDICATION MIXING CENTER IN A NEONATAL INTENSIVE CARE UNIT - Lucília Feliciano Marques; Cristiano Bertolossi Marta; Roberto Carlos Lyra da Silva; Antônio Augusto de Freitas Peregrino; Carlos Roberto Lyra da Silva; Vivian Schutz (Universidade Federal do Paraná, 2019)
Objective: To analyze the cost-effectiveness of the intravenous medication mixing center in reducing dose errors in the preparation of injectable medications in neonatal intensive care. Method: mathematical model proposed in 2017 to assess cost-effectiveness by comparing two health technologies in hypothetical scenarios using the TreeAge® 2011 Pro Suite Software. A Monte Carlo simulation was used to analyze the robustness of the model. Results: the model predicted that the intravenous medication mixing center was cost-effective, with a mean effectiveness of 0.96 in avoiding dose errors in intravenous drug administration, with an incremental cost-effectiveness ratio of R$26,785.61. Conclusion: the use of an intravenous medication mixing center was the most cost-effective alternative, considering the willingness to pay assumed in the model. The study may contribute to reducing uncertainty in decision making regarding the incorporation of dose error reduction technologies in medication administration in pediatric and neonatal ICUs.